An investigation of high temperature tensile properties of selective laser melted Ti-6AL-4V - Baitimerov, R. M. (2018)
Ti-6Al-4V alloy is successfully used in selective laser melting (SLM) especially for production of metal dental and surgical prostheses. On the other hand Ti-6Al-4V alloy is widely used in aerospace industry including applications with temperatures up to 350°C (623 K). In this work, for investigation of high temperature tensile properties, Ti-6Al-4V alloy tensile specimens were fabricated by selective laser melting. Tensile tests were carried out at room and elevated temperatures (up to 350°C). For all considered temperatures, SLM fabricated Ti-6Al-4V shown more strength and less ductility in comparison with wrought material.